79‐5: Late-News Paper: Ultra‐thin Variable Transmission Smart Window by One‐step Patterned Photoalignment. Issue 1 (30th May 2018) - Pan, Su; Meng, Cuiling; Tseng, Man Chun; Tang, Shu Tuen; Kwok, Hoi Sing
Abstract : Smart windows are attractive because of their numerous advantages such as elegance in construction design and energy conservation. Smart windows with variable transmission are especially desirable for obvious reasons. The simplest way to make a variable transmission smart window is to use two patterned polarizers, and control the transmission by changing the relative position of the two polarizers. We have demonstrated a high‐dichroic‐ratio polarizer by photoalignment and proposed a simple one‐step photo‐copy method to realize a continuous axis varying polarizer. The patterned polarizer shows high optical performance, and its thickness is as thin as 100 nm, which is favorable in practical window applications.